Fighting eimeriosis by using the anti-eimerial and anti-apoptotic properties of rhatany root extract - Al-Quraishy, Saleh; Abdel-Gaber, Rewaida; Alamari, Ghada; Meryk, Andreas; El-Ashram, Saeed; Al-Shaebi, Esam M.; Dkhil, Mohamed A. (Frontiers in Immunology, 2024)
Background Over the last decade, extensive use of coccidiostats to treat and control Eimeria infection has developed drug resistance, prompting the search for new alternative therapies. Rhatany is proven to have various pharmacological properties. Objective The present study aimed to in vitro and in vivo evaluate the effect of Rhatany roots extract (RRE) as an anti-eimerial and anti-apoptotic agent against murine eimeriosis induced by Eimeria papillata. Methods Phytochemical screening by gas chromatography-mass spectrometry analysis (GC-MS) was used to detect active compounds in RRE. In vitro anti-eimerial activity of RRE (200, 100, 50 mg/ml), amprolium, phenol, Dettol™, and formalin were studied after incubation with non-sporulated Eimeria oocysts. For the in vivo study, twenty-five male C57BL/6 mice were randomly allocated into five groups. Animals in the first group were just given distilled H2O, while those in the second group were given 200 mg/kg RRE for 5 days. The Eimeria parasite’s oocysts were infected into the third, fourth, and fifth groups. For treatment, RRE (200 mg/kg) and amprolium (120 mg/kg) were orally given to the 4th and 5th groups for five days, respectively. All mice were euthanized, on day 5 post-infection, to collect the jejunal tissues under study. Investigations were undertaken into the oocyst output in feces and goblet cells in mice jejuna. Assays for glutathione peroxidase (GPx), hydrogen peroxide (H2O2), and myeloperoxidase (MPO) were also performed. In jejunal tissue, cysteine aspartic acid protease-3 (Caspase-3) was counted using immunohistochemistry, while BCL2-associated X protein (Bax) and B-cell lymphoma-2 (BCL-2) were assayed using ELISA. In addition, mRNA expression of the goblet cell response gene (MUC2) was detected using real-time PCR. Results Phytochemical screening by GC-MS demonstrated the presence of 22 compounds in the RRE. The in vitro study revealed that RRE significantly inhabited the oocyst sporulation in a dose-dependent manner. By day 5 after infection with the Eimeria parasite, the number of oocysts in mice feces was significantly reduced after RRE treatment (1.308 × 106 ± 1.36 × 105 oocysts/g feces) compared to the infected group (5.387 × 106 ± 4.29 × 105 oocysts/g feces). Moreover, the Eimeria infection reduced the number of goblet cells of mice jejuna and its specific gene, MUC2. The treatment with RRE increased the number of goblet cells/villus from 3.45 ± 0.17 to 6.04 ± 0.23, associated with upregulation for MUC2 from 0.26 to 2.39-fold. Also, the Eimeria experimental infection lowered the activity of the antioxidant enzyme represented by GPx (23.99 ± 3.68 mg/g tissue), while increasing the stress parameters of hydrogen peroxide (0.07 ± 0.01 mM/g) as well as the activity of MPO (66.30 ± 3.74 U/mg). The production of apoptotic markers including Caspase-3 (68.89 ± 2.67 U/g) and Bax (159.05 ± 6.50 pg/ml) was significantly elevated while decreasing the anti-apoptotic marker of BCL2 (0.42 ± 0.07 pg/ml). Our study proved that RRE significantly reduced oxidative stress, and apoptotic markers as well as the inflammatory activity of MPO. Also, antioxidant enzyme and anti-apoptotic activity in the jejunum of E. papillata-infected mice were enhanced after RRE treatment. Conclusion Our study highlights the potential of RRE as a natural solution for coccidiosis management by modulating apoptosis in E. papillata host cells. However, further research is needed to fully understand the underlying mechanisms and enhance our understanding of its therapeutic efficacy.